Electrochemical and spectroelectrochemical properties of new metal free, nickel(II), lead(II) and zinc(II) phthalocyanines - KOCA, ATIF (ELSEVIER SCIENCE SA, 2016)
The new metal free, nickel(II), lead(II) and zinc(II) phthalocyanines containing 2-[2-(4-allyl-2-methoxyphenoxy)ethoxy]ethoxy groups were synthesized and structurally characterized by using IR, H-1 NMR,C-13 NMR, UV-vis and elemental analysis spectral data. Redox properties of the complexes were determined with voltammetric and in situ spectroelectrochemical measurements in different electrolytic systems, tetrabutylammonium perchlorate (TBAP) dissolved dichloromethane (DCM) and dimethylsulfoxide (DMSO). All complexes gave two reversible reduction couples in the cathodic sides of the voltammograms in TBAP/DCM. While two oxidation processes were observed for all complexes in DCM, these processes were recorded as broad and split waves. All of the redox processes of the complexes shifted to the negative potentials and behaved more reversible in TBAP/DMSO electrolyte. Due to the narrow anodic potential window of DMSO, only one oxidation process was recorded in DMSO, while third reduction processes could be observed at more negative potentials for all complexes. Changing of the metal center of the complexes caused to shifting of the redox processes due to the different effective nuclear charge on the metal ions of the complexes. It can be easily concluded that the results of the voltammetric and in situ spectroelectrochemical supported the proposed structure of the complexes. (C) 2016 Published by Elsevier B.V.
Keywords: Phthalocyanine; Metal free; Nickel; Lead; Zinc; Electrochemistry; Spectroelectrochemistry; IN-SITU SPECTROELECTROCHEMISTRY; METALLOPHTHALOCYANINES; COBALT; CO(II); FILMS